'Bridging the gap between the intellectual and the human': The awkward biography of anthropologist and scholar-activist Iona Simon Mayer (1923–). Issue 2 (3rd April 2019) - Bank, Andrew
ABSTRACT: This article tracks the coming together of anti-apartheid activism, feminism and humanism in the life and work of the social anthropologist and scholar-activist Iona Simon Mayer (1923–). Her biography is acutely awkward given her inner conflict and subsequent scholarly debate about the degree of acknowledgement that was due to her as a collaborator with her husband Philip during his fieldwork in Kenya in the late 1940s, but especially in the analysis and writing of Townsmen or Tribesmen (1961), a famous ethnography on the resilience of 'Red' Xhosa culture in East London. The article seeks to balance a recognition of the creative work that Iona achieved with her much-loved husband across decades of joint fieldwork, analysis and writing with her hitherto entirely unacknowledged independent contributions to African ethnography, closely associated with her involvement in a Black Sash feminist circle in Grahamstown of the 1970s. Iona's feminism was of a more modern mould than that of the South African-born women who pioneered the field of social anthropology in the region in that it involved a vehement critique of patriarchy in African culture, drawing creatively on a dynamic new literature on the anthropology of performance but articulated in a typically eloquent denunciation of 'hard-edged' authoritarian power structures. Above all, the article tracks what Mayer retrospectively identified as an inner tension between 'the intellectual' and 'the human' across her anthropological career, making a case for a liberating period of resolution through her inter-related work as an anti-apartheid activist and feminist anthropologist.